Effect of Domestic Sewage on Phytoplankton Community in River Rapti at Gorakhpur - Kushwaha VB; Agrahari M (International Journal of Life Sciences, 2015)
This paper aims to study the effect of domestic sewage on phytoplankton population in river Rapti at Gorakhpur, U.P. and India. An increase in free CO2, bicarbonate alkalinity, nitrate, phosphate and BOD while a decrease in pH, DO and carbonate alkalinity was observed at sewage mixing point. However, these parameters gradually changed at the station away from sewage mixing point (downstream) and were within the limits of Indian standards. During the study period total 29 species of phytoplanktons were observed belonging to 4 families: Bacillariophyceae (11), Chlorophyceae (10), Cyanophyceae (6) and Euglenophyceae (2). In present investigation it was observed that population of phytoplankton was very low at station R2 where sewage mixed into river.